Seeking risk or answering smart? Framing in elementary schools - Valentin Wagner (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
This paper investigates how framing manipulations affect the quantity and quality of decisions. In a field experiment in elementary schools, 1.377 pupils are randomly assigned to one of three conditions in a multiple-choice test: (i) gain frame (Control), (ii) loss frame (Loss) and (iii) gain frame with a downward shift of the point scale (Negative). On average, pupils in both treatment groups answer significantly more questions correctly compared to the "traditional grading". This increase is driven by two different mechanisms. While pupils in the Loss Treatment increase significantly the quantity of answered questions - seek more risk - pupils in the Negative Treatment seem to increase the quality of answers - answer more accurately. Moreover, differentiating pupils by their initial ability shows that a downward shift of the point scale is superior to loss framing. High-performers increase performance in both treatment groups but motivation is significantly crowded out for low-performers only in the Loss Treatment.
Keywords: D03; I20; D80; C93; M54; 330; behavioral decision making; quantity and quality of decisions; framing; loss aversion; field experiment; motivation; education